دور المساءلة الإدارية في مكافحة الفساد المالي في المشاريع الهندسية الحكومية (Comprehensive Journal of Science, 2025)
The study aimed to identify the role of administrative accountability in combating financial corruption within governmental engineering projects, and to examine the extent to which the theoretical framework of administrative accountability is capable of limiting manifestations of financial corruption in such projects. It further sought to identify the theoretical shortcomings within accountability mechanisms that may contribute to the persistence of corrupt financial practices throughout the different stages of governmental engineering projects. The study also explored how theoretical literature explains the relationship between the complexity of governmental engineering projects and the limited effectiveness of administrative accountability in addressing financial irregularities. In addition, it examined the theoretical factors related to institutional, technological, and organizational environments that constrain the effectiveness of administrative accountability in fulfilling its supervisory and deterrent roles against financial corruption in engineering projects.The descriptive method was adopted due to its suitability for the study’s objectives.The study reached the following conclusions:The effectiveness of administrative accountability in combating financial corruption is fundamentally linked to the institutional environment.The technical and technological complexity of engineering projects constitutes a major obstacle to effective administrative accountability.The current regulatory framework places excessive emphasis on procedural compliance and formal organizational requirements, with insufficient focus on actual project outcomes and execution quality.Weak integration between internal and external oversight entities increases the likelihood of persistent financial corruption.
Keywords: Administrative Accountability – Combating Financial Corruption – Engineering Projects.